Role of Histone Deacetylase Rpd3 in Regulating rRNA Gene Transcription and Nucleolar Structure in Yeast - Oakes, Melanie L. (American Society for Microbiology, 2006)
The 35S rRNA genes at the RDN1 locus in Saccharomyces cerevisiae can be transcribed by RNA polymerase (Pol) II in addition to Pol I, but Pol II transcription is usually silenced. The deletion of RRN9 encoding an essential subunit of the Pol I transcription factor, upstream activation factor, is known to abolish Pol I transcription and derepress Pol II transcription of rRNA genes, giving rise to polymerase switched (PSW) variants. We found that deletion of histone deacetylase gene RPD3 inhibits the appearance of PSW variants in rrn9 deletion mutants. This inhibition can be explained by the observed specific inhibition of Pol II transcription of rRNA genes by the rpd3Δ mutation. We propose that Rpd3 plays a role in the maintenance of an rRNA gene chromatin structure(s) that allows Pol II transcription of rRNA genes, which may explain the apparently paradoxical previous observation that rpd3 mutations increase, rather than decrease, silencing of reporter Pol II genes inserted in rRNA genes. We have additionally demonstrated that Rpd3 is not required for inhibition of Pol I transcription by rapamycin, supporting the model that Tor-dependent repression of the active form of rRNA genes during entry into stationary phase is Rpd3 independent.